Small molecule-based highly active and selective K⁺ transporters with potent anticancer activities - Zhang, Hao (2023)
We report here a novel class of cation transporters with extreme simplicity, opening a whole new dimension of scientific research for finding small molecule-based cation transporters for therapeutic applications. Comprising three modular components (a headgroup, a flexible alkyl chain-derived body, and a crown ether-derived foot for ion binding), these transporters efficiently (EC50 = 0.18-0.41 mol % relative to lipid) and selectively (K+/Na+ selectivity = 7.0-9.5) move K+ ions across the membrane. Importantly, the most active (EC50 = 0.18-0.22 mol %) and highly selective series of transporters A12, B12, and C12 concurrently possess potent anticancer activities with IC50 values as low as 4.35 ± 0.91 and 6.00 ± 0.13 μM toward HeLa and PC3 cells, respectively. Notably, a mere replacement of the 18-crown-6 unit in the structure with 12-crown-4 or 15-crown-5 units completely annihilates the cation-transporting ability.